2021
DOI: 10.1111/jocn.15703
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of selecting gluteal injection site on the pain injection based on anthropometric indices and body shape pattern: A randomised controlled trial study

Abstract: Aims and Objectives This study was aimed at comparing the effect of injection site selection based on anthropometric indices and body shape pattern on pain injection. Background Pain is one of the common complications of intramuscular injection. Selecting the right place for gluteal injection is one of the challenges of nursing which can increase the safety and success of the injection and thereby reduce the pain severity caused by it. Design Open‐label randomized controlled trial study. Methods In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It was concluded that these initiatives provide positive results in increasing the effectiveness of education. In the literature, there are some studies about nurses' choices of site for IM injection (8,9,10,22), pain control (23) and needle length to be used (6), whereas studies examining skill levels are limited (16,24). In this study, the skill levels of the nurses were objectively observed and evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that these initiatives provide positive results in increasing the effectiveness of education. In the literature, there are some studies about nurses' choices of site for IM injection (8,9,10,22), pain control (23) and needle length to be used (6), whereas studies examining skill levels are limited (16,24). In this study, the skill levels of the nurses were objectively observed and evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the most common complication related to injections is pain (Sahebkar et al, 2021). Penetration of the skin by the needle, mechanical and chemical effects of the drug and physical characteristics of the patient are non‐modifiable pain risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed analysis of the literature did not reflect a unanimous view in dorso vs ventro debate. Some authors argument that when accurately identified, an injection into the DS carries no greater risk (Larkin et al, 2018; Sahebkar et al, 2021). The safety of the ventrogluteal site has also generated doubts.…”
Section: Discussionmentioning
confidence: 99%
“…There are 5 potential IM injection sites: deltoid (commonly used for adult vaccinations), dorsogluteal (upper outer quadrant), ventrogluteal (side of the hip), and rectus femoris and vastus lateralis (thigh) [ 5 ]. Selecting the optimal location for gluteal injection is important to ensure the safety and success of the injection and to minimize pain [ 6 ]. Although preference for the dorsogluteal site has been reported, the ventrogluteal region is safer for IM injection as the site is free of major nerves and blood vessels, with subcutaneous adipose tissue thin enough to reach target muscles [ 5 , 7–9 ].…”
mentioning
confidence: 99%